Penilaian Daya Dukung Sungai Antirogo di Kabupaten Jember terhadap Beban Pencemaran Menggunakan Metode Streeter-Phelps - Sri Wahyuningsih; Elida Novita; Deni Agung Idayana (agriTECH, 2020)
The Antirogo River is a tributary of Bedadung Watershed which flows from Tegal Gede Village to Sumbersari Village, Jember Regency, East Java. The land areas near the River is used for agriculture, residential settlements, and industry. The wastes dumped from these lands degrades the water quality. Therefore, this study aimed to determine the river capacity against pollution loads, using the Streeter Phelps method in accordance with the Decree of Environment State Minister No. 110 of 2003. Water samples was taken from the River and divided into four monitoring points namely ATR01, ATR02, ATR03, and ATR04. A purposive sampling method was used and the water quality was analyzed. The average pollution load is 70.37 kg/day. Furthermore, the highest load is 81.04kg/day at ATR03 and the lowest is 64.81 kg/day at ATR04. Therefore, the river’s capacity can be determined by calculating the reaeration and deoxygenation rate, critical oxygen deficit, distance, and time taken to reach a point. The average deoxygenation rate is 1.77 mg/L.day, and that of reaeration is 16.13 mg/L.day. Also, the DOact values at ATR01, ATR02, ATR03, and ATR04 were 6.59 mg/L, 6.67 mg/L, 6.63 mg/L, and 6.67 mg/L respectively. The average value of oxygen deficit is 1.19 mg/L. According to the values of deoxygenation, reaeration, oxygen deficit, and DOact, it can be interpreted that the river is not in a critical condition, and, therefore, can tolerate pollutant load of 7.26 kg/day.